Event driven energy depth and channel aware routing for underwater acoustic sensor networks: Agent oriented clustering based approach. (February 2017) - Bharamagoudra, Manjula R.; Manvi, SunilKumar S.; Gonen, Bilal
Highlights: Employment of multiple routing parameters such as energy, propagation time, link quality, hop count and queue size in an integrated manner. The cluster heads are selected based on the speed of data transmission that vary with the depth of node placement, temperature, and salinity of water environment. A cross layer approach is adopted to estimate the link quality. To avoid the void conditions and improve the scalability, 3D deterministic deployment scheme is considered. Adoption of agent based routing scheme with flexible and customized services. Graphical abstract: The objective of the paper is to develop an agent based routing scheme with following features. (1) Increased Lifetime of network, (2) Reduced Latency, (3) Void Avoidance, (4) Reliable neighbor discovery, and (5) Connectivity enhancement during link breakdown. In order to realize the objectives, we define an agent based routing scheme that has intelligence embedded in it to take autonomous decisions and act intelligently. Abstract: An energy efficient channel aware and depth based scalable and multipath agent based routing protocol is proposed in this paper. We consider a scenario consisting of underwater sensor nodes, autonomous underwater vehicles (AUV), underwater gateways, and surface gateways deployed at the territory to monitor the ocean environment (temperature, salinity and pressure) and detect the intruder (moving or static object). Dynamic clustering process is initiated on occurrence of an event; sensor nodes in the event affected area facilitate collection and aggregation of data by the cluster head. The cluster head initiates routing scheme by using mobile agent and its clones to discover multiple paths to a surface gateway based on parameters such as node energy, hop count, propagation delay and channel quality. In order to improve network connectivity and reliability in case of network partitions, an agent based dynamic AUV traversal algorithm is proposed to reorient direction of AUV movement.